o AUTO CAMONIANO D’EL REI SELEUCO: AS POÉTICAS DO AUTO - CAPÍTULO DE UM ESTUDO INÉDITO SOBRE O TEATRO CAMONIANO. - Casado Gomes, Francisco (Revista Letras, 1980)
One can notice the influence of Aristotle’s Poetics on this play ("Auto"), a destiny drama, in which one sees Epicureanism, stoicism and mercantilism throughout the narrative expressed in the "classical" form, due to the quantitative equilibrium of its two grand sequences and to its five opposite but resolutive acts, in which one tries to solve the problems created by the Mannerism influenced epochal code. There a,re also recollections of Aeschylus, Euripedes, Horatio, Castiglione and the authors of the Cancioneiro Geral, of Garcia de Resende and Gil Vicente and Sá de Miranda’s plays. The play does not present the humanistic euphoria but it has man (the lover) as its chief concern. There is only one cardine,I function that repeats itself in the play ("Auto"): come-go, and this determines some few subordinating scenes, alongside which other coordinated and equipollent scenes appear,- there are 254 lines in the eight prose scenes, and the part of the "figures in earnest" ("figuras de sino" — eighteen scenes) has 731 verses, distributed in stanzas of five verses (127), stanzas of six verses (6), triplets (3), quartets (2), stanza of ten verses (1), a stanza of twelve verses an three loose verses.